Immunology : a short course - Benjamini, Eli (John Wiley, 2000)
Immunology is the study of how humans and animals biologically protect themselves from disease. This textbook has been updated to include two chapters of information on "Cytokines" and "Immune Responses to Infections". There has been an extensive revision of material to reflect the many advances in our knowledge of certain immunological concepts including: T and B cell responses to antigen, antigen processing and presentation, vaccination technology, immunotherapy, and mechanisms responsible for immune disorders, including immunodeficiencies. Aimed primarily at medical students, the layout has maintained its supplementary learning style but updated its content. There are review questions at the end of each chapter and clinical case scenarios to enable students to practice problem-solving exercises using the knowledge objectives associated with specific chapters. Traditional multiple-choice questions have been modified by integrating concepts which build upon preceding chapters in the book. There is also a supplemental website.